2015
DOI: 10.4236/ajac.2015.63023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Olive Leaves Drying on the Content of Oleuropein

Abstract: Oleuropein content in olive leaves dried at ambient temperature, and at elevated temperature (50˚C) from Palestinian olive trees collected from West Bank in the middle of November was determined by HPLC and compared to naturally dry olive leaves (collected dry from the tree). Results showed that higher concentration was obtained from olive leaves dried at room temperature (10.0 mg per gram of dry olive leaves), compared to those dried at 50˚C (1.7 mg/g), and those that collected dry from the tree (2.5 mg/g). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 6 publications
1
25
0
Order By: Relevance
“…However, it is also evident that this comparison needs to consider the influence of other factors that might affect the oleuropein and phenolic compounds in olive leaf extracts, including the olive cultivar, leaf color/ age, time (season) of collection, and the drying and storage conditions (Afaneh, Yateem, & Al-Rimawi, 2015;Blasi et al, 2016;Ranalli et al, 2006;Wang, Gao, Ye, Chen, & Jiang, 2008).…”
Section: Ultrasound-assisted Extraction Optimizationmentioning
confidence: 99%
“…However, it is also evident that this comparison needs to consider the influence of other factors that might affect the oleuropein and phenolic compounds in olive leaf extracts, including the olive cultivar, leaf color/ age, time (season) of collection, and the drying and storage conditions (Afaneh, Yateem, & Al-Rimawi, 2015;Blasi et al, 2016;Ranalli et al, 2006;Wang, Gao, Ye, Chen, & Jiang, 2008).…”
Section: Ultrasound-assisted Extraction Optimizationmentioning
confidence: 99%
“…It was observed statistically significant differences between all olive leaves and drying methods compared to control groups ( p < .01). Afaneh et al () determined 0.19 mg/g, 15.6 mg/g, and 19 mg/g oleuropein in ethyl acetat, ethanol/water, and acetonitrile/water extracts of olive leave. In previous study, Afaneh et al () determined 1.7 mg/g oleuropein in leave dried at 50 °C, 2.5 mg/g oleuropein in leave dried in air, 10 mg/g oleuropein in leave dried at 25 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Afaneh et al () determined 0.19 mg/g, 15.6 mg/g, and 19 mg/g oleuropein in ethyl acetat, ethanol/water, and acetonitrile/water extracts of olive leave. In previous study, Afaneh et al () determined 1.7 mg/g oleuropein in leave dried at 50 °C, 2.5 mg/g oleuropein in leave dried in air, 10 mg/g oleuropein in leave dried at 25 °C. Ansari, Kazemipour, and Fathi () reported that olive leaves contained 6.1–13.3 mg/g oleuropein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main compound of biophenol in olive is oleuropein which is widely studied, because it has wide spectrum of health applications in diseases such as blood pressure [12], heart disease [13], bacterial infections, viral infections [14], and cancer [15,16]. Amount of oleuropein in ripe fruit is more than growing fruit [17]. Different factors such as extraction method, type of solvent, temperature, and extraction time affect efficiency.…”
Section: Introductionmentioning
confidence: 99%